2010
DOI: 10.1007/s10072-010-0330-5
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of GSTT1, GSTM1 genotype polymorphisms and serum total GST activity with ischemic stroke risk

Abstract: Oxidative stress plays a major role in pathogenesis of atherosclerosis which is responsible for stroke. Glutathione S-transferases (GSTs) detoxify metabolites produced by oxidative stress within the cell and protect the cells against injury. This study aimed to investigate the association of polymorphisms in GSTT1, GSTM1 genes and GST activity with ischemic stroke risk. Patients had almost the same GST activity as that of controls. No significant differences were found between patients and controls in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Stroke patients who present lower GST activity might be a susceptibility factor for oxidative stress injury [13] [14,15,16]. In Caucasians GSTT1 and GSTM1 null genotype incidence are 13-26 and 42-60 %, respectively [17,18]. Our results are in concordance with previous studies.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Stroke patients who present lower GST activity might be a susceptibility factor for oxidative stress injury [13] [14,15,16]. In Caucasians GSTT1 and GSTM1 null genotype incidence are 13-26 and 42-60 %, respectively [17,18]. Our results are in concordance with previous studies.…”
Section: Discussionsupporting
confidence: 95%
“…Polonikov et al [20] showed that no differences were observed with GSTM1 and GSTP1 gene polymorphisms and a significant difference was observed in GSTT1 null genotypes (OR 1.51, 95 % CI 1.09-2.07, p \ 0.001). However, Polonikov et al's data were inconsistent with the results of a recent association study, which did not find any significant associations between the GSTM1 and GSTT1 null genotypes and ischemic cerebrovascular disease in a large cohort of Danish patients [21] and other studies [11,13,17,19,22]. Shyu et al investigated the association between DNA gene-repair gene polymorphism and LAA stroke risk.…”
Section: Discussionmentioning
confidence: 94%
“…(catalyzing the conversion of H 2 O 2 to water and oxygen), while GST catalyzes a variety of reactions that detoxify endogenous compounds, including peroxidized lipids (Das and Bishayi 2010;Turkanoglu et al 2010). We found that both CAT activity and cat expression decreased with oxygen depletion.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, the case group was composed of Caucasian individuals who had suffered from ischemic stroke in the study by Türkanoğlu et al (2010), who found an overall lower prevalence of the GSTM1 present genotype (49.4% (N = 172) and 43.8% (N = 105) for the case and control groups, respectively). In addition, there was no significant differences between case and control groups.…”
Section: Discussionmentioning
confidence: 89%